Characteristics of winning men's and women's sevens rugby teams throughout the knockout Cup stages of international tournaments - Barkell, J. F.; O'Connor, D.; Cotton, W. G. (International Journal of Performance Analysis in Sport, 2016)
Identification of game variables associated with success in men's and women's sevens rugby tournaments is required to assist in tactical preparation for future competition. The aim of this study was to analyse the game variables associated with winning teams in knockout Cup games and identify if winning characteristics are gender specific. All quarter final and semi-final games from the men's (n=54) and women's (n=30) 2014 World Sevens Series tournaments were analysed using a set of game variables associated with sevens performance. Comparisons between teams were examined through a series of Mann Whitney U Tests and Independent t-tests